Determination of moisture diffusivity and activation energy on fixed bed drying of red pepper (Capsicum annum) on convective solar drying - Siti Asmaniyah Mardiyani; Sumardi Hadi Sumarlan; Bambang Dwi Argo; Amin Setyo Leksono (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Moisture diffusivity and activation energy are two important variables in a drying process to understand a certain product's drying behavior. This study aimed to determine the value of effective moisture diffusivity and the activation energy of red pepper in a conventional forced convective drying based on electricity (conventional convective drying/CCD) and forced convective drying based on solar energy (convective solar drying/CSD). The value of effective moisture diffusivity was determined using the equation, which refers to Fick’s second law. The Arrhenius equation determines the activation energy value as a model of the relationship of inverse temperature and the normal logarithmic value of effective moisture diffusivity. The results showed that the values of effective moisture diffusivity of CCD 70 °C were the highest. The regression analysis between the drying layers (X), and effective moisture diffusivity (Y) showed a polynomial pattern with a coefficient determination R2 value of 0.85 (CCD 70 °C), 0.81 (CCD 60 °C), 0.88 (CCD 50 °C), and 0.48 (CSD). (R2) The higher moisture diffusivity values in CCD indicated that the drying systems are more stable than CSD. The drying activation energy calculation showed that the value of CCD's activation energy was 36.36 kJ/mol.K, while the value of CSD's activation energy was 31.28 kJ/mol.K. Those results were consistent with the results of the previous studies.